THE EVALUATION OF THE BACHELOR OF NURSING SCIENCE PROGRAM (REVISED CURRICULUM, B.E. 2554) OF POLICE NURSING COLLEGE - Thawitsri, Nuanla-or; Paha, Khemika; Sanee, Pranee (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
This research is a descriptive study to present the evaluation results of the Bachelor of Nursing Science Program (Curriculum Revised B.E. 2554), Police Nursing College, Police General Hospital, Royal Thai Police referred to a concept of CIPP Model. The samples were administrators, nursing instructors, nursing students, and nursing graduates, and stakeholders. The research instruments were questionnaires for administrators, nursing instructors, nursing students, and nursing graduates, and interview forms for stakeholders, which had been examined for content validity, IOC, equaled to 1.00 on every questionnaire. The Cronbach alpha coefficients were .86, .92, .94, .89 and .93, respectively. The data were analyzed using frequency, percentage, mean, and standard deviation. The results of the research found that: 1) The context, the objectives of the curriculum were consistent with the desirable characteristics of the graduates at a high level, 2) The input, the course structure was appropriate at a high level. The subjects in the curriculum and their grouping were moderately appropriate. The contents of the curriculum were up to date and corresponded to the current social conditions at a high level. However, the curriculum structure and content of the curriculum were not able to clearly identify the identity of the Police Nursing College, 3) The process, the course administration was at a moderate level. It had standardized student selection. The number of students was appropriate for the number of teachers in an 8:1 ratio, 4) Student productivity, the view of stakeholder to the nursing graduates was that the graduates can perform their jobs at a high level. Thus, the improvements of the Bachelor of Nursing Science Program should focus on designing a curriculum and course structure that reinforces the identity of the Police Nursing College to be clear and concrete.